Pengembangan LKPD Berbasis Liveworksheets pada Mata Pelajaran PAI Materi Mawaris di Kelas XII SMK Negeri 1 Belitang Madang Raya - Magfira, Nurul; Romdloni, Romdloni; Suwandi, Suwandi (Pendidikan Islam Anak Usia Dini STIT Palapa Nusantara, 2026)
The limited availability of interactive digital student worksheets (LKPD) on mawaris material presents a challenge in Islamic Religious Education learning, although this material plays an important role in improving students’ conceptual understanding. This study aimed to describe the process of developing Liveworksheets-based LKPD on mawaris material, test the level of product validity, and assess its practicality based on teacher and student responses. This study used the Research and Development (R&D) method with the 4D model, which includes the stages of define, design, develop, and disseminate. The research subjects consisted of one material expert, one media expert, one Islamic Religious Education teacher, and 34 twelfth-grade vocational high school students selected using purposive sampling. Data were collected through validation sheets, practicality questionnaires, and interviews, and were then analyzed using quantitative descriptive techniques. The results showed that the developed LKPD had a very high level of validity, with a score of 83.33% from the material expert and 94.67% from the media expert, as well as an average validity of 89%. In terms of practicality, the teacher response reached 100% and the student response reached 86.76%, with an average of 93.38%, thus categorized as highly practical. Therefore, the Liveworksheets-based LKPD on mawaris material was declared feasible and practical for use in Islamic Religious Education learning. This study provides a theoretical contribution to the development of digital teaching materials as well as practical implications for educators in utilizing interactive LKPD to improve the quality of learning.